National Identity and Ideology: A Critical Discourse Analysis of Prabowo’s UN Speech - Nabila, Maulina; Rosalina, Utami (Jurnal sosial dan sains, 2025)
The speech delivered by Indonesia’s Minister of Defense and President-elect, Prabowo Subianto, at the 80th United Nations General Assembly on September 23, 2025, in New York, has drawn significant national and international attention for its emphasis on self-reliance, global justice, and nationalistic values. This study aims to reveal the representation of national identity and the underlying political ideology embedded in the speech through Norman Fairclough’s model of Critical Discourse Analysis (CDA). The primary data were obtained from the official video recording of the speech released through government media channels, as well as from a verified transcript. The analysis focuses on three main dimensions text, discourse practice, and social practice to identify how language functions as an ideological instrument in constructing Indonesia’s national image within an international forum. The findings indicate that Prabowo employs linguistic strategies that highlight global solidarity while underscoring national sovereignty, reflecting a moderate nationalism intertwined with the discourse of global justice. In conclusion, the speech serves not only as a form of diplomatic communication but also as a symbolic representation of Indonesia’s national identity within the framework of contemporary geopolitics.